2019
DOI: 10.32734/injar.v2i2.1154
|View full text |Cite
|
Sign up to set email alerts
|

Free Choice Feeding on the Quality of Quail Eggs (Coturnix coturnix-japonica)

Abstract: Quail is one of the potential sources of animal protein from poultry as egg producers. An egg contains complete nutrients, namely protein, fat, vitamins, and minerals. As food, eggs must be maintained both physically and chemically to be safe for consumption. This study aimeds to examine the effect of selective feeding on the quality of quail eggs. This research was carried out at Percut Sei Tuan Subdistrict, Deli Serdang Regency, North Sumatra, which had been implemented from August to November in 2018. The s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
2
0
2
Order By: Relevance
“…The chemical composition of quail egg yolk is presented in Table-5 . Japanese quail eggs have a higher crude protein, crude fat, and mineral ash content per unit egg weight than chicken eggs and other popular poultry, such as pheasant and guinea fowl [ 46 ]. Another study by Oviawe et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The chemical composition of quail egg yolk is presented in Table-5 . Japanese quail eggs have a higher crude protein, crude fat, and mineral ash content per unit egg weight than chicken eggs and other popular poultry, such as pheasant and guinea fowl [ 46 ]. Another study by Oviawe et al .…”
Section: Discussionmentioning
confidence: 99%
“…The chemical composition of quail egg yolk is presented in Table-5. Japanese quail eggs have a higher crude protein, crude fat, and mineral ash content per unit egg weight than chicken eggs and other popular poultry, such as pheasant and guinea fowl [46]. Another study by Oviawe et al [47] reported that the proximate composition of whole quail eggs, namely, ash, carbohydrate, fat, protein, and moisture, were 1.06, 4.01, 9.89, 12.7, and 72.25 g 100 g 1 , respectively, and the energy obtained from whole eggs was 156.50 kcal 100 g 1 .…”
Section: Egg Yolk Chemical Compositionmentioning
confidence: 98%
“…Konsumsi pakan harian menunjukkan tidak berbeda nyata karena memiliki komposisi dan rasa yang sama pada pakan standar yang diberikan pada semua keturunan F1 betina puyuh jepang (kelompok perlakuan). Pakan yang diberikan pada ternak juga harus disesuaikan dengan umur dan kebutuhan ternak (Silaban, et al 2019). Faktorfaktor lain yang mempengaruhi konsumsi pakan yaitu kesehatan ternak, aktivitas ternak, energi ransum, tingkat produksi, kualitas dan kuantitas pakan (Nuraini et al, 2012;Silaban et al, 2019) Konsumsi minum harian keturunan F1 betina dari induk yang diberi suplemen tepung kunyit hasil analisis datanya menunjukkan tidak berbeda nyata (P > 0,05).…”
Section: Hasil Dan Pembahasanunclassified
“…Pakan yang diberikan pada ternak juga harus disesuaikan dengan umur dan kebutuhan ternak (Silaban, et al 2019). Faktorfaktor lain yang mempengaruhi konsumsi pakan yaitu kesehatan ternak, aktivitas ternak, energi ransum, tingkat produksi, kualitas dan kuantitas pakan (Nuraini et al, 2012;Silaban et al, 2019) Konsumsi minum harian keturunan F1 betina dari induk yang diberi suplemen tepung kunyit hasil analisis datanya menunjukkan tidak berbeda nyata (P > 0,05). Hal ini disebabkan karena tidak terdapat perbedaan konsumsi pakan harian dan kondisi lingkungan yang sama.…”
Section: Hasil Dan Pembahasanunclassified